Effect of boron on growth and flowering of African marigold (Tagetes erecta) cv. Pusa Narangi Gainda - SHEELA LIPINAYAK; GEETA PANDEY; ASHISH KUMAR GOUDA; RAKESH KUMAR; SUBRAT KUMAR SENAPATI (Journal of Ornamental Horticulture, 2024)
An investigation was carried out to study the impact of boron on growth and flowering of African marigold (Tagetes erecta) cv. Pusa Narangi Gainda in experimental field of the College of Agriculture, Odisha University of Agriculture and Technology, Bhubaneswar, Odisha during November, 2018 to March, 2019. The study employed a randomized block design with eight treatments and three replications. The treatments included foliar and soil applications of boron at varying concentrations and frequencies and indicated significant variations in vegetative and flowering parameters across treatments. Notably, treatment T7 (soil application of B @ 0.5 kg ha–1) exhibited the highest plant height (84.35 cm), length of primary branches (49.94 cm) and stem girth (4.5 cm). Treatment T4 (foliar spray B @ 0.25% once) displayed the maximum number of primary branches (10.17 cm), while T8 (soil application (0.25 kg ha–1 + foliar spray B @ 0.15%)) recorded the highest number of secondary branches (26.73). Flower characteristics also varied significantly among treatments, with T5 (foliar spray B @ 0.25% twice) leading in flower diameter (6.51 cm). Also, the minimum (46.63 days) days to flowering, minimum (50.23 days) days to 50 per cent flowering, minimum (54.29 days) days to 100 per cent flowering and minimum (42.97 days) days to bud showing colour was recorded under T4 (foliar spray B @ 0.25% once). Number of flowers per plant, yield of flowers per plant and yield per plot were found maximum (83.17, 195.44 g and 2.25 kg/m2 respectively) with T5.